Wavelet‐based individual blade pitch control for vibration control of wind turbine blades. Issue 1 (19th October 2018) - Fitzgerald, Breiffni; Staino, Andrea; Basu, Biswajit
Summary: This paper proposes a novel individual blade pitch control strategy with the objective of reducing blade vibration. A wavelet linear quadratic regulator (LQR) control algorithm, which is an advanced modification of the conventional LQR controller, has been developed for this purpose. The formulation of the modified LQR algorithm uses the information derived from wavelet analysis of the blade response in real time to obtain the local energy distribution over frequency bands. This information, reflecting the effect of excitation on the blades, is used to design the pitch controller by updating the weighting matrices to be applied to the response energy and the control effort. The proposed control algorithm does not require a priori choice of the weights as in the classical case and calculates the gains using the weights based on the response characteristics in real time. The optimal LQR control problem is solved for each time interval with updated weighting matrices, through the Ricatti equation, leading to time‐varying gain matrices. Simulations are carried out using the National Renewable Energy Laboratory's (NREL) high‐fidelity FAST wind turbine simulation model. The simulations indicate that the proposed new wavelet controller achieves significant reduction in the out‐of‐plane response of the blades as compared with standard LQR or industry standard proportional integral (PI) controllers, at the expense of minor increases in rotational speed variability and increased pitch actuator usage.